# The simplest form, in therms of i.What is simplest form, in therms of i. (i+6)(5i^2-5)

*print*Print*list*Cite

### 2 Answers

To simplify (i+6)(5i^2-5), first notice that we have i^2, this is equal to -1.

So we have (i+6)(5i^2-5)

=> (i + 6)(-5 - 5)

=> (i + 6)(-10)

Open the brackets and multiply

=> -10i - 10*6

=> -10i - 60

**The required simplified form of (i+6)(5i^2-5) is -10i - 60.**

We'll have to multiply the pairs of brackets and we'll apply the distributive property of multiplication, over addition.

For the beginning, we notice that the second factor contains the term i^2 = -1.

(i+6)(5i^2-5) = (i+6)(-5-5)

(i+6)(5i^2-5) = -10(i + 6)

(i+6)(5i^2-5) = -10*i - 10*6

(i+6)(5i^2-5) = -60 - 10i

**The simplest form, in terms of i, of the given expresison is:**

(i+6)(5i^2-5)** = **-60 - 10i